Empowerment of the Marine Task Force for Safeguarding the Outer Islands to Increase Development of Maritime Potential in the Border Area, especially the North Natuna Sea - Oke Aditya; Ahmad Fauzi (Jurnal Perikanan dan Kelautan, 2022)
The purpose of this study is to describe the empowerment of the marine task force in carrying out the security task force for the outer islands, the authority of the role of the marine task force in maritime development, the regulatory authority for the role of the marine task force to improve the development of maritime potential in the North Natuna Sea border area. The method used is qualitative research. Analysis using data analysis techniques Soft System Methodology (SSM). The results showed that the communication of related stakeholders was well established and constructive, the efforts were made by having limited defense capabilities against attacks; supervisory ability; and the ability to prevent the transit of illegal activities. For Maritime Development in the North Natuna Sea Border Area, Assistant Dankormar Col. Mar is responsible to the Marine Corps Commander in carrying out his daily tasks. The Indonesian Navy agency in the Natuna Region to compile a Regulation on the implementation of the Marine Task Force in increasing maritime potential development.